Effectiveness of different methods of decontamination of endodontic instruments - Popović Jelena; Gašić Jovanka; Stojilković Goran; Dačić Stefan (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: There is an increasing awareness of the risk of iatrogenic transmission of prion diseases, since this infective agent has shown resistance to conventional procedures of chemical and thermal decontamination and sterilisation. Aim: The aim of the study was to evaluate the effectiveness of different methods for biological debris removal from the surfaces of endodontic instruments and to suggest an efficient protocol for cleansing prior to sterilization. Materials and Methods: Eighty four new endodontic instruments were used for hand instrumentation of the root canals in extracted teeth in order to accumulate organic debris. The instruments were allocated to four groups and subjected to different methods of decontamination: mechanical cleansing with a brush and sponge, chemical dissolution in sodium hypochlorite (NaOCl) and enzyme cleanser, ultrasonic treatment in water and disinfectant and the combination of the most effective mechanical, chemical and ultrasonic methods. The instruments were stained in the Van Gieson solution which efficiently stains the organic component and then analyzed under a light microscope. Results: Effectiveness was evaluated based on the amount of residual organic material. The analysis of pairs of methods with similar effects showed significant differences between mechanical cleansing with a brush and sponge and ultrasonic treatment in water and disinfectant. No difference was found between treatments in NaOCl and enzyme cleanser. The combined method was significantly more efficient than the other methods. Conclusion: The most efficient protocol for endodontic instrument decontamination consists of mechanical cleansing with a sponge soaked in chlor hexidine, chemical treatment in the enzyme cleanser and ultrasonic treatment in an appropriate disinfectant.